The role of urine albumin creatinine ratio and serum β2 microglobulin as biomarkers of chronic kidney disease - Eguvbe, Augustine Onovuakpo; Nwagu, Marcellinus Uchechukwu; Idogun, Eshiotseme Sylvester; Akande, Adeyinka Abdulrasaq (Universa Medicina, 2019)
BACKGROUNDChronic kidney disease (CKD) is an increasing burden on individuals and on the healthcare system. The need to identify more sensitive and specific markers of CKD cannot be overemphasized to facilitate detection and appropriate intervention. β2 microglobulin is one of such markers of CKD. The aim of this study was to investigate the sensitivities and specificities of serum β2 microglobulin and major biochemical markers of CKD, namely creatinine and urine albumin. METHODSThis was a hospital-based cross-sectional study involving 124 subjects with CKD and 124 healthy controls. Participants were categorized in two groups : group 1 the CKD based on persistent reduction in GFR <60 mL/min/1.73 m2 and group 2 healthy subjects as controls. Blood (serum) samples of participants were analyzed for serum creatinine and serum β2 microglobulin while their urine samples were analyzed for creatinine and albumin. Urine albumin creatinine ratio (UACR) was calculated from the results of the analyses. RESULTSThere was a very strong positive correlation of serum β2 microglobulin with serum creatinine (r=0.750; p=0.000) and UACR (r=0.775; p=0.000), respectively. Also, there was a very strong negative correlation between serum β2 microglobulin and eGFR (r=-0.866; p=0.000). UACR had the highest sensitivity and specificity as shown by receiver operating curve characteristics (ROC) analysis. CONCLUSIONIn CKD, UACR and serum β2 microglobulin had the best diagnostic value. Periodic renal assessment of renal patients is mandatory as they may be affected by hidden renal dysfunction.